(untitled) (Economics and region, 2021)
The scientific literature was analyzed in the article, which allowed the systematizing of modern models and methods of the enterprise economic development on the basic combinations of theoretical approaches and concepts of management, the practice of enterprises management under modern conditions. Directions of the specified models’ researches and methods were revealed. These areas are based on the concepts of business process modeling, reengineering, benchmarking, enterprise restructuring. It was proposed to implement the model of economic development taking into account various factors: a model of economic development through business processes modeling, model of economic development based on reengineering, method of benchmarking, method of restructuring. It was proved the relevance of the modern models of economic enterprises development introduction in order to eliminate technological backwardness of Ukraine from developed European countries. Our further researches will be connected with the definition of the most effective models of economic development for concrete enterprises in real economic conditions of their activity.